PRODUKSI PADI DAN JAGUNG DALAM EKONOMI RUMAH TANGGA PETANI LAHAN SAWAH: MODEL DAN SIMULASI KEBIJAKAN (Studi Kasus Di Desa Kepuh Kembeng Kecamatan Peterongan Kabupaten Jombang) - Setiani Setiani (MediaTrend, 2015)
This study aimsto analyzemodel and impact ofpolicy simulationin riceandmaizeproduction werecarried out bywet land farm households. The study was conductedin Kepuh Kembengvillage PeteronganDistrict Jombang Regency, East Java Province. This study using simultaneous equationsmodel and analyzed by syslin 2SLS. The results showedthat farm householdsproductionof riceandmaizeaffected bythe use ofinputssuch aslabor, ureaandTSP fertilizers. Farm householdrice and maize productiondetermineearned of totalprofit. Simulationsubsidypolicy of increasingprices of fertilizersmake lowerrice andcorncost production, finally increase profitabilityof rice, cornandtotalprofits of farm household.